2010
DOI: 10.1175/2010jcli3171.1
|View full text |Cite
|
Sign up to set email alerts
|

Subtropics-Related Interannual Sea Surface Temperature Variability in the Central Equatorial Pacific

Abstract: Interannual sea surface temperature (SST) variability in the central equatorial Pacific consists of a component related to eastern Pacific SST variations (called Type-1 SST variability) and a component not related to them (called Type-2 SST variability). Lead–lagged regression and ocean surface-layer temperature balance analyses were performed to contrast their control mechanisms. Type-1 variability is part of the canonical, which is characterized by SST anomalies extending from the South American coast to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
200
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(223 citation statements)
references
References 37 publications
22
200
1
Order By: Relevance
“…In our methodology the coupling of tropical Pacific sea surface temperature-eastern African rainfall variability emerges from the data, and this shift in the influence region agrees well with previous studies that identify an increase in the intensity of central Pacific (CP) ENSO in the future from GCM outputs (Kim and Yu, 2012). While CP ENSO is thought to be forced by changes in the atmospheric circulation, the mechanism for eastern Pacific ENSO is rather associated with thermocline variations in the oceanic circulation (Yu et al, 2010), and the seasonal impacts produced by these two types of ENSO could differ. For example, wetter patterns of EP El Niño events in eastern Africa might not occur under CP El Niño events, and CP La Niña events could induce drier conditions in the southern parts of the region than EP La Niña events (Wiedermann et al, 2017), which could result in prolongated drought events for the eastern African region.…”
Section: Scenario Selection and Future Simulationssupporting
confidence: 88%
“…In our methodology the coupling of tropical Pacific sea surface temperature-eastern African rainfall variability emerges from the data, and this shift in the influence region agrees well with previous studies that identify an increase in the intensity of central Pacific (CP) ENSO in the future from GCM outputs (Kim and Yu, 2012). While CP ENSO is thought to be forced by changes in the atmospheric circulation, the mechanism for eastern Pacific ENSO is rather associated with thermocline variations in the oceanic circulation (Yu et al, 2010), and the seasonal impacts produced by these two types of ENSO could differ. For example, wetter patterns of EP El Niño events in eastern Africa might not occur under CP El Niño events, and CP La Niña events could induce drier conditions in the southern parts of the region than EP La Niña events (Wiedermann et al, 2017), which could result in prolongated drought events for the eastern African region.…”
Section: Scenario Selection and Future Simulationssupporting
confidence: 88%
“…1b). Yu and Kao (2007) also noticed there are two different types of ENSO, moreover, Kao and Yu (2009) and Yu et al (2010) explain the different mechanisms which lead to the different two kinds of El Niño events. Ashok et al (2007) found that the evolution of El Niño Modoki events is related to a tripolar pattern of sea level pressure anomalies, and noted the presence of two anomalous Walker circulation cells associated with El Niño Modoki events, versus the single cell that is associated with canonical El Niño events.…”
Section: Introductionmentioning
confidence: 96%
“…Yu et al [14] and Yu and Kim [15] found that the EP-ENSO is possibly produced by the delayed oscillator or the recharged oscillator after they have examined the structure of subsurface ocean temperature (SOT), but the possible linkage between the CP-ENSO and the SOT variations is still unclear. In this regard, the aim of this study is to identify the possible linkage between the two types ENSO events and the variations in the SOT anomalies, particularly on the interdecadal time scale.…”
mentioning
confidence: 99%